Status of stigma on the health care workers related to COVID-19 at the first wave of the pandemic in Iran: A qualitative study - Badrfam, Rahim; Qorbani, Mostafa; Zandifar, Atefeh (Frontiers in Psychiatry, 2022)
Background: Stigma can be seen as a mark of disgrace that can lead to the separation of one person from another. In this qualitative study, we assess the status of stigma among in front-line health care workers (HCWs) during the first wave of the COVID-19 pandemic in Iran. Subjects and Methods: The participants were selected from frontline HCWs related to COVID-19 in Imam Ali and Imam Hossein referral hospitals in Alborz province, Iran. Study was conducted between May and June 2020. The 32-item checklist Consolidated Criteria for Reporting Qualitative Research (COREQ) was used to report this qualitative study. Interview questions were prepared based on the grounded theory method.The thematic approach was used to analyze the data content. Data analysis was based on open and axial coding and after implementing the codes in MAXQDA software. Results: The results of this study included 4 themes, 8 categories and 33 sub-categories. Themes included extrinsic and intrinsic elements of stigma, perplexity and stigma removal requirements. Extrinsic elements included "creating blame and shame" and "discrimination" categories. Intrinsic elements included “the desire to be avoidance”, “feeling depressed and frustrated” and “feeling anxious and scared” categories. Perplexity included "feeling loss" category. Stigma removal requirements included “factors causing stigma” and “protective agents against stigma” categories. Conclusion: Low public awareness on COVID-19 and inadequate public care, limited personal protective equipment and inadequate facilities for HCWs along with lack of appreciation for their efforts, lack of proper psychiatric/psychological counseling to identify and treat symptoms associated with mental health and the limitations of training to maintain mental health skills are considered to be factors in the formation of stigma among HCWs related to COVID-19. Health policymakers should implement coherent strategies related to increasing public awareness and providing personal protection needs and counseling care for HCWs in relation to COVID-19.